Emergency Nursing Management Model for Patients with Critical Illness: A Theoretical Study - Yusriani Saleh Baso; Basyarul Haqiqi; Ady Irawan. AM; Sri Yulian Hunowu (Indonesian Journal Publisher, 2025)
This study aims to analyze and describe theoretical models used in emergency nursing management for critically ill patients. Employing a qualitative design with a descriptive approach through systematic literature review, data were collected from academic journals, official documents, and relevant theoretical frameworks, selected based on credibility and recency. The analysis applied inductive methods involving theme identification, data reduction, conceptual categorization, and synthesis. Findings reveal that structured nursing models such as HIRAID, the AACN Synergy Model, Levine’s Conservation Model, and specialized roles like the T2 Nurse and Advanced Practice Nurses (APNs) significantly improve clinical decision-making, documentation accuracy, patient safety, and care efficiency. These models also enhance cultural responsiveness, ethical reasoning, and interprofessional collaboration. Despite these benefits, challenges such as workload pressures, ethical dilemmas, and omission of care remain barriers to optimal implementation. The study concludes that the integration of flexible, theory-based, and evidence-driven nursing models contributes meaningfully to emergency nursing practice and scientific development, while also calling for further cross-setting validation and longitudinal research to strengthen model applicability in diverse healthcare environments.